Logical Framework Analysis dalam Pemberdayaan Masyarakat yang Berkelanjutan: Studi pada Program Pengembangan dan Pemberdayaan Masyarakat di PT Bukit Asam - Humaedi, Sahadi; Apsari, Nurliana Cipta; Adiansah, Wandi; Santoso, Meilanny; Raharjo, Santoso Tri; Kamal , Mustfa (Warta LPM, 2023)
Community development and empowerment program (PPM) is form of corporate social and environmental responsibility as an effort to provide benefits to the environment around the company, especially the community. The PPM program is designed to create various positive changes in society both for the people who are around the company and society in general. In its implementation, the company needs to make clear planning, development, supervision, and monitoring of the program objectives. Logical Framework Analysis (LFA) is one of the tools used in determining management planning and industrial evaluation of the program to be implemented by identifying the relationships between existing elements to a conclusion. The purpose of this study is to describe the process of using Logical Framework Analysis which is applied and used in planning community empowerment programs in state-owned mining companies located in Tanjung Enim, South Sumatra Province, which carry out Community Development and Empowerment Programs in the manufacturing sector. Following the mandate of Law no. 40 of 2007 concerning Limited Liability Companies, companies that carry out their business activities in the natural resources sector are required to carry out Social and Environmental Responsibility. The research method used in this research is a qualitative descriptive method so that it can clearly describe the process of preparing a Logical Framework Analysis. The data collection process is carried out through in-depth interviews and focus group discussions (FGD) with stakeholders related to manufacturing, fisheries, and livestock programs. Apart from in-depth interviews and FGDs, secondary data collection was also carried out as a form of validating the data obtained directly. The research results show that LFA can be designed after analyzing the roles and interests of each relevant stakeholder, especially in the manufacturing sector, analyzing the situation, and analyzing the problems surrounding the PPM program in the manufacturing sector. PT Bukit Asam Tbk's PPM Manufacturing Program has used LFA to ensure that the program runs and can make the beneficiary communities independent of the program.